A Study on the Application of Wax on Linden (Tilia tomentosa Moench.) Wood - Hüseyin Peker; Göksel Ulay; Ümit Ayata (Wood Research Journal, 2024)
Linden wood is used in match production, double bass making, carving, musical instrument crafting, and furniture production. This study examined the effects of applying varying numbers of wax coats (1, 2, and 3 coats) on the color parameters, glossiness values, and whiteness index (WI*) values of linden (Tilia tomentosa Moench.) wood surfaces. A comparison was made between untreated surfaces and those treated with three different wax applications. According to the obtained results, all tests except for hue angle were found to be significant in the analysis of variance. The ∆E* values were found to be 5.13 for the application of 1 coat of wax, 6.53 for the application of 2 coats of wax, and 6.95 for the application of 3 coats of wax. After applying waxes to the wood, reductions were noted in WI* and L* values, while enhancements were detected in glossiness readings at 60 and 85 degrees, as well as in a*, C*, ho, and b*values.